Palhada residual de cana-de-açúcar (Saccharum spp) colhida mecanicamente (sem queima prévia): manejo, fertilização, influência no perfilhamento e produtividade da cultura - Caldeira, Daniela Soares Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The aim of this work was to verify the green cane (Saccharum spp) harvesting unburned trash interference in budding, tilling, growth, yield and clay soil fertility during a three years period. Different fertilizers were applied to the trash surface in three distinct procedures. Trash was managed in order to be unaltered on the soil (M1); trash was completely withdrawn from soil (M2); trash was withdrawn only from planting line (M3). The used fertilizers were urea (T2), filter cake (T3), vinasse (T4), vinasse + urea (T5), filter cake + urea (T6) and no fertilizers (T1), in order to verify the these treatments behavior along the cultivation years. The research was performed in Igaraçu do Tietê city, in the State of São Paulo, in an area owned by a sugarcane plant named Usina da Barra. The RB806043 was used in the third harvest and the adopted experimental delineating was randomized blocks, factorial scheme 3X6 in three repetitions, totaling 54 experimental splittings of 70 m2 . Chemical soil evaluations were performed, and through a monthly survey of the tilling number the budding and tilling evaluation were performed. The parameters considered were the total number of culms per splitting; average culm weight; average culm height and diameter; industrialized culm yield; culm technological analysis and the amount of trash related to the residual yield of this culture. Data were submitted to the variance analysis and compared by the Tukey test. The experimental group analysis was performed to verify the results combination in the three experimental years. Significantly variations that could indicate the effect of the treatment on the soil fertility were not observed, excluding K and P that showed increasing values in the treatments where vinasse and filter cake were applied...(Complete abstract, click electronic access below)
Keywords: Cana-de-açúcar; Solos - Manejo; Fertilizantes nitrogenados; Residuos agricolas; Green cane; Sugarcane